MANAGEMENT OF BLAST [PYRICULARIA GRISEA (COOKE) SACC.] DISEASE OF PEARL MILLET THROUGH FUNGICIDES - H. D. JOSHI; N. M. GOHEL (The Bioscan, 2015)
Blast of pearl millet has emerged as serious disease affecting both grain and fodder production in pearl millet. Among the nine fungicides and two antibiotics at three concentrations were evaluated under in vitro condition by poisoned food technique against Pyricularia grisea revealed, propiconazole, mancozeb, tricyclazole and carbendazim (12%) + mancozeb (63%) at all the three concentrations completely inhibited the mycelial growth of the pathogen and proved to be most effective. Based on in vitro screening, promising fungicides were selected and re-evaluated under field condition against blast of pearl millet. Experiment under field condition revealed that two foliar sprays at an interval of 15 days commencing from the first initiation of disease with tricyclazole, 0.05% or iprobenfos, 0.1% or isoprothiolane, 0.05% was most effective in reducing blast intensity (17.78, 33.59 and 38.19% DI) and increasing grain (3493, 3012 and 2968 kg/ha) and fodder yield (6918, 5383 and 5323 kg/ha, respectively) over control (83.68% DI, grain yield 2483 kg/ha and fodder yield 3338 kg/ha).